STRENGTHENING COOPERATION BETWEEN THE CENTER OF RESEARCH RURAL AND REGIONAL DEVELOPMENT OF SEBELAS MARET UNIVERSITY WITH THE KEDIRI REGENCY GOVERNMENT - Muhammad Hendri Nuryadi; Itok Dwi Kurniawan; Ismawati Septiningsih; Wahyu Noviansyah; Fitri Handayani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Globalization influences public service delivery through technological and informational revolutions, while regional autonomy demands its implementation to be aligned with local potential and needs. To evaluate and improve governance, PUSLITDESBANGDA UNS employs quantitative analysis with strategic management and SWOT approaches. This research is conducted over six months in 2024, involving internal and external sources, including the Kediri Regency Government. Data collection methods include observation, in-depth interviews, questionnaires, and FGDs. Main activities comprise FGDs, BUMDes workshops, and village tourism branding studies. The outcomes are expected to enhance professionalism, managerial skills, transparency, and access to external financial resources for BUMDes. Additionally, the program aims to optimize PUSLITDESBANGDA branding and strengthen research and community service collaborations with various stakeholders. Outputs from this activity include articles in ISSN journals, online media articles, and publicized activity videos. The evaluation results are expected to improve PUSLITDESBANGDA's performance in supporting sustainable development and the quality of life in rural communities.